2019
DOI: 10.1038/s41598-019-40140-5
|View full text |Cite
|
Sign up to set email alerts
|

Relative abundance of Akkermansia spp. and other bacterial phylotypes correlates with anxiety- and depressive-like behavior following social defeat in mice

Abstract: As discussion of stress and stress-related disorders rapidly extends beyond the brain, gut microbiota have emerged as a promising contributor to individual differences in the risk of illness, disease course, and treatment response. Here, we employed chronic mild social defeat stress and 16S rRNA gene metagenomic sequencing to investigate the role of microbial composition in mediating anxiety- and depressive-like behavior. In socially defeated animals, we found significant reductions in the overall diversity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 49 publications
12
72
0
Order By: Relevance
“…Of note, EAP did reduce the relative levels of phylum Deferribacteres, class Deferribacteres, order Deferribacterales, and family Deferribacteraceae. This result aligns with recent reports of alteration in the relative abundance of phylum Deferribacteres in chronic social defeat stress‐induced depression model 40 . Collectively, dysbiosis in microbiotas play an important role in depressive‐like behaviors in EAP mice.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, EAP did reduce the relative levels of phylum Deferribacteres, class Deferribacteres, order Deferribacterales, and family Deferribacteraceae. This result aligns with recent reports of alteration in the relative abundance of phylum Deferribacteres in chronic social defeat stress‐induced depression model 40 . Collectively, dysbiosis in microbiotas play an important role in depressive‐like behaviors in EAP mice.…”
Section: Discussionsupporting
confidence: 92%
“…One possibility is that DHA-induced Bifidobacterium and Lactobacillus reduce opioid-seeking behavior through microbiome-brain signaling, consistent with literature demonstrating anxiolytic properties of specific strains within these genera [20,62]. DHA may also work by suppressing bacteria such as Akkermansia that can induce anxiety-like behavior [63].…”
Section: Discussionsupporting
confidence: 58%
“…10 Furthermore, Lactobacillus rhamnosus 4B15 and bioactive peptides derived through microbial proteolysis of glycated casein could have an important role in these protective effects, based on previous studies on introducing bacteria or gut contents and their consequences on brain structure and functions including behavior. 39 The milk-derived opioid peptide casoxin C (κ-casein f (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), Tyr-Ile-Pro-Ile-Gln-Tyr-Val-Leu-Ser-Arg) was reported to possess psychoactive properties with hormonal and neurotransmitter activities. 40 In our previous study, several peptides that composed in FGc were demonstrated their biological functions such as antioxidative, antimicrobial, immunomodulatory, anti-hypertensive, and ACE inhibitory activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, the microbial diversity (alpha-diversity) was significantly decreased by exposure to stress or psychiatric disorders, such as ADHD. 29,30 However, the behavior tests were likely to act as physical stressors to mice (stressed mice as well as non-stressed mice) in this study. 31 In terms of microbiota composition, principal-coordinate analysis and UniFrac unweighted pair-group method with arithmetic mean cluster analysis using phylogenetic distance, for beta-diversity, showed distinct clustering of samples with the non-stressed control (N-Con), stressed and Gc-treated (S-Gc), and stressed and FGc-treated (S-FGc) groups clustered more closely and separated from the stressed control (S-Con) and stressed and fluoxetine-treated (S-Flu) groups ( Figure 5A, B).…”
Section: Fgc Normalized Ucms-induced Alteration Of the Microbiotamentioning
confidence: 99%